2020
DOI: 10.4274/eajem.galenos.2019.07108
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analyses of Frequent Emergency Department Users

Abstract: Aim: Emergency department (ED) demand and overcrowding is increasing worldwide, and a significant portion of this overcrowding is caused by ''frequent users''. The aim of the study is to define the characteristics of this group of patients who contribute towards a disproportionate number of ED visits. Materials and Methods: All ED visits during a 1-year period between 01 January 2018 and 31 December 2018 were retrospectively investigated using the electronic registration system of the hospital. Patients who vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Turkey is a country that normally has overcrowded EDs, and many of the applications comprise nonspecific complaints, which are “nonemergent” in reality [ 4 ]. This study showed a sharp reduction at applications to the ED due to nonspecific complaints after the declaration of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Turkey is a country that normally has overcrowded EDs, and many of the applications comprise nonspecific complaints, which are “nonemergent” in reality [ 4 ]. This study showed a sharp reduction at applications to the ED due to nonspecific complaints after the declaration of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Turkey, with high emergency department (ED) demand and overcrowded EDs, is a country whose annual number of ED visits is greater than the whole population [ 4 ]. After announcement of the first coronavirus case in Turkey on March 11th, measures such as the termination of international flights, closing of schools, closing of all public gathering places, and curfews for special age groups and metropolitan municipalities were taken by the government to prevent the spread of the disease [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, annual ED visits per 1000 population are around 430 in the USA 25 and 390 in England. 26 While these vast numbers of visits can be associated with various national, cultural, and economic reasons, the most common reasons in Turkey are: that emergency care is free of charge, and the most straightforward route to a hospital bed is through EDs, 27 , 28 frequent users, 29 , 30 no appointment requirement, 24 , 31 providing uninterrupted ED service while all other hospital and polyclinics provide service only within working hours. 30 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the default state of overcrowded healthcare systems, statistics from other countries have shown a reduction in the ED patient volume early in the COVID-19 pandemic [5]. It has been shown that, in some studies, the patterns of ED visits also changed significantly during the pandemic season [6][7][8]. However, most of these studies were planned from data from the first year of the fight against COVID-19.…”
Section: Introductionmentioning
confidence: 99%